Bone Defects in Tibia Managed by the Bifocal vs. Trifocal Bone Transport Technique: A Retrospective Comparative Study - Abulaiti, Alimujiang; Liu, Yanshi; Cai, Feiyu; Liu, Kai; Abula, Abulaiti; Maimaiti, Xiayimaierdan; Ren, Peng; Yusufu, Aihemaitijiang (Frontiers in Surgery, 2022)
Background The purpose of this study is to evaluate the clinical effectiveness and determine the differences, if any, between the trifocal bone transport (TFT) technique and the bifocal bone transport (BFT) technique in the reconstruction of long segmental tibial bone defects caused by infection using a monolateral rail external fixator. Methods A total of 53 consecutive patients with long segmental tibial bone defects caused by infection and treated by monolateral rail external fixator in our department were retrospectively collected and analyzed from the period January 2013 to April 2019, including 39 males and 14 females with an average age of 38.8 ± 12.4 years (range 19–65 years). Out of these, 32 patients were treated by the BFT technique, and the remaining 21 patients were managed by the TFT technique. The demographic data, operation duration (OD), docking time (DT), external fixation time (EFT), and external fixation index (EFI) were documented and analyzed. Difficulties that occur during the treatment were classified according to Paley. The clinical outcomes were evaluated by following the Association for the Study and Application of the Method of Ilizarov (ASAMI) criteria at the last clinical visit. Results All patients achieved an infection-free union finally, and there was no significant difference between the two groups in terms of demographic data and both ASAMI bone and functional scores (p > 0.05). The mean defect size and OD in TFT (9.4 ± 1.5 cm, 161.9 ± 8.9 min) were larger than that in BFT (7.8 ± 1.8 cm, 122.5 ± 11.2 min) (p < 0.05). The mean DT, EFT, and EFI in TFT (65.9 ± 10.8 days, 328.0 ± 57.2 days, 34.8 ± 2.1 days/cm) were all less than those in BFT (96.8 ± 22.6 days, 474.5 ± 103.2 days, 60.8 ± 1.9 days/cm) (p < 0.05). Difficulties and complications were more prevalent in the BFT group than in the TFT group (p < 0.05). Conclusion Both the trifocal and BFT techniques achieve satisfactory clinical outcomes in the reconstruction of long segmental tibial bone defects caused by infection using a monolateral rail external fixator. The TFT technique can significantly decrease the DT, EFT, EFI, difficulties, and complications compared with the BFT technique.